Dynamical properties of z similar to 2 star-forming galaxies and a universal star formation relation - Bouche, N; Cresci, G; Eisenhauer, F; Schreiber, N; Genzel, R; Gillessen, S; Lehnert, M; Lutz, D; Nesvadba, N; Shapiro, K; Sternberg, A; Tacconi, L; et al. (Institute of Physics Publishing, 2007)
We present the first comparison of the dynamical properties of different samples of z ∼ 1.4-3.4 star-forming galaxies from spatially resolved imaging spectroscopy from SINFONI/VLT integral field spectroscopy and IRAM CO millimeter interferometry. Our samples include 16 rest-frame UV-selected, 16 rest-frame optically selected, and 13 submillimeter galaxies (SMGs). We find that rest-frame UV and optically bright (K < 20) z ∼ 2 star forming galaxies are dynamically similar, and follow the same velocity-size relation as disk galaxies at z ∼ 0. In the theoretical framework of rotating disks forming from dissipative collapse in dark matter halos, the two samples require a spin parameter 〈λ〉 ranging from 0.06 to 0.2. In contrast, bright SMGs (S850 μm ≥ 5 mJy) have larger velocity widths and are much more compact. Hence, SMGs have lower angular momenta and higher matter densities than either the UV or optically selected populations. This indicates that dissipative major mergers may dominate the SMGs population, resulting in early spheroids, and that a significant fraction of the UV/optically bright galaxies have evolved less violently, either in a series of minor mergers, or in rapid dissipative collapse from the halo, given that either process may leads to the formation of early disks. These early disks may later evolve into spheroids via disk instabilities or mergers. Because of their small sizes and large densities, SMGs lie at the high surface density end of a universal (out to z = 2.5) "SchmidtKennicutt" relation between gas surface density and star formation rate surface density. The best-fit relation suggests that the star formation rate per unit area scales as the surface gas density to a power of ∼ 1.7, and that the star formation efficiency increases by a factor of 4 between non-starbursts and strong starbursts. © 2007. The American Astronomical Society. All rights reserved.